The Right to Disagree: Judges, Juries, and the Administration of Criminal Justice in Maryland - Gary J. Jacobsohn (Washington University Law Quarterly, 1976)
It is now generally believed that justice will best be served if juries decide only questions of fact, leaving judges as the final arbiters of matters of law. In Maryland and Indiana, however, juries retain constitutional authority to act as judges of law as well as of fact. This Article will examine this once common but now nearly extinct practice, and explore the desirability of its retention. The focus is upon article XV, section 5, of the Maryland Constitution, which provides that “In the trial of all criminal cases, the Jury shall be the Judges of Law, as well as of fact, except that the Court may pass upon the sufficiency of the evidence to sustain a conviction.”
Keywords: Administration of criminal justice; Constitutional law – Maryland; Judicial statistics; Juries